Design of a Floating Curved Photovoltaic Panel with IoT-Enabled Weather Monitoring for Rivers and Lakes Environments - J. Baeren, Erold; Al-Humairi, Safaa Najah Saud (Al-Khwarizmi Engineering Journal, 2026)
Floating photovoltaic (PV) systems enable solar energy generation on water bodies, alleviating land scarcity whilst providing potential cooling and reflection benefits that enhance panel performance. However, many floating installations employ flat PV modules without optical concentration or integrated tracking, which limits their energy yield in tropical environments such as rivers and lakes. This study designs a floating solar platform that incorporates a curved PV configuration mounted on a buoyant platform, a single-axis sun-tracking mechanism and an IoT-based weather and performance monitoring system designed for riverine deployment. This prototype employs an 18 V, 250 W monocrystalline flexible solar panel formed into a curved trough that is controlled by an Arduino-based tracking system and a NodeMCU-based monitoring subsystem to record voltage, temperature and humidity via a mobile application. Experimental testing on the Damansara River indicates that the floating curved system achieves a maximum power output of 231±5 W, which is higher compared with the output of a flat-land-based configuration (190±7), corresponding to an efficiency enhancement of approximately 21% at a solar radiation intensity of 1200 W/m². The floating configuration also exhibits reduced efficiency degradation with increasing ambient temperature due to the cooling effect of the water body and elevated humidity, which together mitigate thermally induced performance losses. These findings demonstrate that the proposed curved floating solar platform provides a feasible and environmentally friendly solution for increasing PV energy yield whilst conserving land resources in tropical regions.